Sistema de escritorios remotos para el desarrollo de laboratorios virtuales en el área de seguridad informática de la UAO (2022)
Due to the current global situation of Covid 19, companies and educational institutions have been forced to migrate to new remote working options to avoid increasing spikes in infections and continue with their economic and / or academic activities. This research’s main objective is to provide a free solution to ensure that the students of the UAO have access to remote virtual computer security laboratories without the need to use high processing costs that these laboratories usually require for their correct and optimal performance. Since for this it is required to mount what is known as virtual machines and these usually demand a high consumption of resources such as last generation processors, large amounts of disk space, consumption of RAM, these requisites limit the option of students with less resources. In order to solve this problem, a deep investigation was carried out on different platforms that offer the creation of remote environments where it is possible to make the respective manipulations to couple the solution with the requirements of the UAO not being requiring high processing costs for the students of said educational institution. To make the system’s design the most suitable tools were selected and implemented to be tested. Finally, due to limitations the mounting was done in small scale in a virtualized environment with the purpose of documentation for future projects and scalability.